2015
DOI: 10.1371/journal.pone.0142204
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Saline Water Drip Irrigation on Tomato Yield, Quality, and Blossom-End Rot Incidence --- A 3a Case Study in the South of China

Abstract: Saline water resources are abundant in the coastal areas of south China. Most of these resources still have not been effectively utilized. A 3-year study on the effects of saline water irrigation on tomato yield, quality and blossom-end rot (BER) was conducted at different lower limits of soil matric potential (-10 kPa, -20 kPa, -30 kPa, -40 kPa and -50 kPa). Saline water differing in electrical conductivity (EC) (3 dS/m, 4 dS/m, 4.5 dS/m, 5 dS/m and 5.5 dS/m) was supplied to the plant after the seedling estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 44 publications
5
59
0
Order By: Relevance
“…Higher yield was in correspondence with higher irrigation quota, this result agreed with the findings of Zhai et al (2015). The yield-increase effects by drip irrigation were also reported in Ayars's and coauthors (1999) study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher yield was in correspondence with higher irrigation quota, this result agreed with the findings of Zhai et al (2015). The yield-increase effects by drip irrigation were also reported in Ayars's and coauthors (1999) study.…”
Section: Discussionsupporting
confidence: 89%
“…For each fruit, 10 g of tomato flesh was taken along the longitudinal axis and then homogenized for quality measurements. The following components contributed greatly to the tomato quality: volume, density, soluble solids, total acid, vitamin C and sugar:acid ratio (Zhai et al, 2015). At each harvest time, the number and weight of tomato was recorded, and the tomato yield was calculated at the end of the last harvest.…”
Section: Methodsmentioning
confidence: 99%
“…Zhai et al [12] emphasized as water is an important impact factor influencing yield and quality of tomato and indicated as yield decreased with increased salinity and recommended that salinity of irrigation water should be controlled under 4 dS/m. In addition, Rahil et al and Magan et al [10,13] reported that total and marketable fruit yield reduced with increasing salinity level.…”
Section: Effect Of Water Quality On Tomato Yieldmentioning
confidence: 99%
“…For instance, in the study conducted in China, it was confirmed that irrigation water more than 5 Ds/m significantly affect the fruit yield of tomato (Zhai et al, 2015). The associated effect of salt in irrigation is attributed to decreased turgor pressure, a lowered speed of cell expansion and damage to chloroplasts, thus reducing the growth rate and photosynthesis.…”
Section: Introductionmentioning
confidence: 97%
“…The use of saline irrigation directly affects the soil profile and the dissolved salts may cause changes in the salt balance of the soil system. Zhai et al (2015) reported that the salt concertation in the soil profile under tomato production was increased by 47% for the use of saline water more than 5 dS/m.…”
Section: Introductionmentioning
confidence: 99%